Preparation method and application of carbon nitride doped phthalocyanine iron activated carbon filled modified cathode
By loading g-C3N4 and FePc on activated carbon particles, an activated carbon filled modified cathode with carbon nitride doped phthalocyanide is prepared, which solves the problems of poor conductivity and slow ORR reaction of traditional cathode materials, and achieves high efficiency of coking wastewater The increase in treatment and H2O2 yield reduces costs.
Patent Information
- Application Number
- CN202411672644.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Traditional cathode materials have poor conductivity, slow ORR reaction, poor stability and high cost, making it difficult to effectively treat coking wastewater.
Using activated carbon particles as support, the activated carbon particles are loaded with g-C3N4 and FePc by acid activation pretreatment, impregnation and calcination to prepare an activated carbon filled modified cathode with carbon nitride doped phthalocyanide for photo/electrocatalytic microbial fuel cell coupling The system carries out coking wastewater treatment and electrocatalytic ORR reaction.
It has achieved efficient treatment of coking wastewater, and the product H2O2 meets the national first-level direct emission standards, which has improved the system's treatment capacity and catalytic performance and reduced costs.
Smart Images

Figure CN119240871A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of industrial wastewater treatment and energy utilization in water pollution control. 3 N 4 Preparation of / AC and its continuous multi-stage treatment of coking wastewater in a photo / electrocatalytic microbial fuel cell coupling system, which can electrocatalyze ORR reaction to produce H 2 O 2 , efficiently remove pollutants from water, and provide ideas and references for the development of efficient, simple and industrially scalable modified cathode catalysts. Background Art
[0002] For microbial fuel cell systems, the choice of electrode materials is a key factor in determining the efficiency of pollutant treatment. Excellent electrode materials should have a large specific surface area to adsorb difficult-to-degrade organic pollutants and have good conductivity to better transfer electrons. Activated carbon particles not only have a large specific surface area and porosity, so that anode microorganisms can attach to them and grow well, but also have excellent conductivity and are cheap and easy to obtain. Compared with traditional metal electrodes, it can reduce costs and has the potential for industrial application. In addition, a major way to improve MFC performance is to increase the cathode ORR reaction rate, increase the level of active substances, and accelerate the oxidation of pollutants.
[0003] Among many semiconductor materials, graphite carbon nitride (gC 3 N 4 ) is a polymer photocatalyst that has attracted much attention due to its non-toxicity, high temperature stability and low-cost precursors. It is suitable for emerging fields such as hydrogen production, carbon dioxide reduction, oxidation of harmful aromatic pollutants, photovoltaic solar cells, and development of gas sensors. 3 N 4 It has high thermal stability, flexible electronic structure, good chemical stability in acids, bases and organic solvents, and a mid-range band gap of about 2.7 eV, corresponding to the 460nm visible light region. 3 N 4 It is active under visible light and provides a flexible channel for photoexcited electron migration. 3 N 4 It is considered to be a promising green photocatalyst and an excellent carrier.
[0004] Metal-based phthalocyanine (Pc) compounds are promising electrode materials for cathode catalysis of ORR. Compared with metal ions, metal phthalocyanines (MPcs) can effectively avoid metal ion overflow. Generally speaking, metal-based (Fe, Co, Ni, etc.) Pc compounds have a transition metal in the center symmetrically surrounded by four nitrogen atoms, which is conducive to the electron transfer between the active sites of the catalyst. Among the transition metals, iron phthalocyanine (FePc) is considered to be the ORR catalyst with the highest electrocatalytic activity. However, FePc molecules often dimerize or polymerize. Due to their strong bonding with each other, FePc is insoluble in water, which reduces the active sites of FePc and affects its catalytic performance. Therefore, in porous gC 3 N 4 Loading FePc can not only enhance the dispersibility, prevent the formation of dimers, and improve the catalytic activity, but also reduce the loss of catalyst.
[0005] The composite catalyst was loaded on activated carbon by a simple impregnation and calcination method and used as a modified filled cathode in a microbial fuel cell system to treat coking wastewater and produce H by electrocatalytic ORR. 2 O 2 , which can not only effectively improve the processing capacity of the system, but also explain the role of the catalyst from the perspective of principle. Summary of the invention
[0006] The purpose of the present invention is to prepare a method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode, and to provide a method for applying the cathode to the practical treatment of coking wastewater and electrocatalytic ORR production of H in a photo / electrocatalytic microbial fuel cell coupling system. 2 O 2 There are two application methods. In order to solve the problems of poor conductivity, slow ORR reaction, poor stability and high cost of traditional cathode materials, activated carbon particles are selected as carriers, and the excellent adsorption of activated carbon is used to convert gC 3 N 4 and FePc loaded on activated carbon particles, and disclosed a simple method for preparing the modified cathode. Furthermore, the efficient treatment of coking wastewater was achieved, the working principle of the system was explained, and the effluent met the direct discharge standard, achieving standard discharge.
[0007] The technical solution of the present invention:
[0008] A method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode, comprising the following steps:
[0009] (1) Acid activation pretreatment of activated carbon particles;
[0010] Furthermore, the acid activation pretreatment process includes: ultrasonic washing with deionized water, drying, acid solution activation immersion, drying, ultrasonic washing with deionized water, and drying;
[0011] Furthermore, the ultrasonic power of the deionized water ultrasonic washing is 80-100W, and the time is 2-4h.
[0012] Furthermore, the drying temperature is 60-80° C. and the drying time is 6-8 hours.
[0013] Furthermore, the acid solution is a nitric acid solution, and the mass fraction of the nitric acid solution is 15% to 20%.
[0014] Furthermore, the activation immersion time is 8 to 10 hours.
[0015] (2) Preparation of FePc / AC: Ferrophthalocyanine was dissolved in anhydrous ethanol, loaded on activated carbon particles after activation pretreatment by impregnation, and then dried to obtain dry ferrophthalocyanine / activated carbon particles;
[0016] Furthermore, the mass fraction of FePc relative to the activated carbon particles is 0.3-0.5wt%.
[0017] Furthermore, an equal volume impregnation method is used for 12 to 24 hours.
[0018] Furthermore, the drying temperature is 60-80° C. and the drying time is 6-8 hours.
[0019] (3)FePc / gC 3 N 4 Preparation of / AC: Urea is dissolved in deionized water, loaded on ferrophthalocyanine / activated carbon particles by impregnation, dried, and then calcined at high temperature in a muffle furnace to obtain carbon nitride-doped ferrophthalocyanine activated carbon.
[0020] Furthermore, the addition ratio of urea is 3-5 wt % relative to the ferrocyanide / activated carbon particles.
[0021] Furthermore, an equal volume impregnation method is used for 12 to 24 hours.
[0022] Furthermore, the drying temperature is 60-80° C. and the drying time is 6-8 hours.
[0023] Furthermore, the working temperature of the muffle furnace calcination is 520-550°C, the heating rate is set to 2-5°C / min, and the calcination time is 3-4h.
[0024] Application of a carbon nitride-doped ferrocyanide activated carbon-filled modified cathode for electrocatalytic ORR to produce H 2 O 2 .
[0025] The invention discloses an application of a modified cathode filled with activated carbon doped with ferrophthalocyanine, which is used to construct a photo / electrocatalytic microbial fuel cell coupling system (PEC / EC-MFC) system. The construction process of the PEC / EC-MFC system is as follows: the system is an upper and lower structure, the upper part is a cathode chamber, the lower part is an anode chamber, an isolation layer is between the anode chamber and the cathode chamber, the isolation layer includes two layers of filter cloth and sand filled between the filter cloths; the operation mode of coking wastewater is bottom-in and top-out; the anode chamber of the PEC / EC-MFC system is filled with activated carbon particles loaded with Shewanella electrogenic bacteria, and an aeration head is used at the bottom to disperse the water; the anode conductive material is a carbon rod, one end of which is connected to a wire and then externally led to a resistor, an ammeter and a cathode material in series in sequence, and the cathode conductive material is a carbon rod; the cathode chamber is filled with activated carbon doped with ferrophthalocyanine, and a visible light source simulating sunlight is added above the cathode when constructing the PEC-MFC.
[0026] An application of a carbon nitride-doped ferrocyanide activated carbon-filled modified cathode for constructing an electrocatalytic ORR system. The construction of the electrocatalytic ORR system: the two electrolytic cells of the double-tank electrolytic cell are separated by an ion exchange membrane, and the anolyte is Na 2 SO 4 solution, the cathode electrolyte is Na 2 SO 4 solution, or the catholyte is a solution with Na 2 SO 4 The diluted coking wastewater was used; a carbon rod was used as the anode, and the prepared carbon nitride-doped ferrophthalocyanine activated carbon was used as the cathode material, and the cathode was connected to the anode through the carbon rod; the cathode material was placed in an insulating container, and the insulating container was connected to the cathode electrolyte; continuous aeration of the cathode ensured a continuous oxygen supply, and continuous ORR experiments were carried out in the constructed electrocatalytic ORR system.
[0027] Beneficial effects of the present invention:
[0028] (1) A method for preparing a filled modified cathode for a photo / electrocatalytic microbial fuel cell coupling system (PEC / EC-MFC) is provided, which can be mass-produced by a simple impregnation and calcination method. The excellent adsorption properties of activated carbon are utilized to compound with the catalyst. After calcination, the activated carbon not only has a smooth surface and an increased void structure, but also can be more stably and tightly combined with the catalyst material.
[0029] (2) Selecting cheap and abundant activated carbon particles as the cathode material carrier, loading gC 3 N 4 and FePc as catalyst materials.
[0030] (3) The material was applied to the PEC / EC-MFC coupling system. When the residence time was 10 h, 50 mg / LS was added to the raw water. 2- or 0.03-0.05 mM Cl - Under the conditions, coking wastewater can be effectively treated and can meet the indirect emission standards; after continuous optimization treatment of aeration, illumination, and addition of PMS, it can meet the national first-level direct emission standards; it is confirmed that the modified filled cathode has excellent catalytic properties and can improve the system's wastewater treatment capacity.
[0031] (4) The material was applied to electrocatalytic ORR, and the product was hydrogen peroxide. In the experiment for 2 h, the best H 2 O 2 The yield reached 62.8mg / h / g cat This indicates that in the PEC / EC-MFC system, the modified cathode can generate H 2 O 2 Then ·OH is produced to oxidize organic pollutants in coking wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The relevant index data diagram of EC-MFC two-stage effluent under raw water conditions; a is the TOC stability diagram; b is the TN stability diagram; c is the COD stability diagram; d is the NH 4 + Stability diagram; the horizontal axis of each diagram is time (h) and the vertical axis is concentration (mg / L).
[0033] Figure 2 Contains 50mg / LS 2- Under the raw water condition, the relevant index data of EC-MFC two-stage effluent; a is the TOC stability diagram; b is the TN stability diagram; c is the COD stability diagram; d is the NH 4 + Stability diagram; the horizontal axis of each diagram is time (h) and the vertical axis is concentration (mg / L).
[0034] Figure 3 The relevant index data of EC-MFC two-stage effluent under the condition of raw water containing 0.03mMCl; a is the TOC stability diagram; b is the TN stability diagram; c is the COD stability diagram; d is the NH 4 + Stability diagram; the horizontal axis of each diagram is time (h) and the vertical axis is concentration (mg / L).
[0035] Figure 4It is a data chart of effluent-related indicators of PEC-MFC in a 4-day continuous experiment, where the light intensity is 50W and the PMS concentration is 0.1mol / L; a is the TOC stability chart; b is the TN stability chart; the horizontal axis of each chart is time (d) and the vertical axis is concentration (mg / L).
[0036] Figure 5 Electrocatalytic ORR produces H 2 O 2 The H of the four groups of comparative experiments 2 O 2 Yield graph, where the horizontal axis is time (min) and the vertical axis is H 2 O 2 The yield (mg / h / g cat ).
[0037] Figure 6a This is a scanning electron microscope (SEM) image of activated carbon particles.
[0038] Figure 6b Fe Pc / gC at 10μm scale 3 N 4 Scanning electron microscope (SEM) image of / AC,
[0039] Figure 6c Fe Pc / gC at 1 μm scale 3 N 4 Scanning electron microscope (SEM) image of / AC,
[0040] Figure 6d Fe Pc / gC at 500nm scale 3 N 4 Scanning electron microscope (SEM) image of / AC.
[0041] Figure 7 FePc / gC 3 N 4 / AC X-ray photoelectron spectrum (XPS) diagram without calcination treatment; where a is the full spectrum; b is the C1s spectrum; c is the N1s spectrum; d is the Fe 2p spectrum.
[0042] Figure 8 FePc / gC 3 N 4 / AC modified cathode X-ray photoelectron spectrum (XPS) diagram; where a is the full spectrum; b is the C1s spectrum; c is the N1s spectrum; d is the Fe 2p spectrum.
[0043] Fig. 9 It is the Fe Pc / gC after the reaction of coking wastewater treated by the system 3 N4 / AC X-ray photoelectron spectrum (XPS) diagram; a is the full spectrum; b is the C1s spectrum; c is the N1s spectrum; d is the Fe 2p spectrum. DETAILED DESCRIPTION
[0044] The following is a further description of the specific implementation of the present invention in combination with the technical scheme and the accompanying drawings, which is not intended to limit the protection scope of the present invention.
[0045] Example 1
[0046] 500g of granular activated carbon was placed in a 1000mL glass beaker, 1000mL of deionized water was added, and ultrasonic washing was performed, followed by draining, and the loss was minimized. The ultrasonic washing operation was repeated three times, and the solution was clarified during the last washing. After washing, the activated carbon particles were dried in a blast drying oven to obtain the activated carbon particles. The equal volume impregnation method was adopted, and a sufficient amount of 20% nitric acid solution was added, and the activated carbon was impregnated for 10 hours, and then dried in a blast drying oven to obtain the acid-activated AC carrier. The ultrasonic washing operation was repeated three times to wash away the residual acid on the surface of the activated carbon carrier, and the catalyst after ultrasonic washing was placed in a blast drying oven to dry. The ultrasonic power of the deionized water ultrasonic washing was 100W, and the time was 3 hours.
[0047] Weigh 1.5 g of ferrophthalocyanine and 500 mL of anhydrous ethanol as solvent, stir thoroughly until the ferrophthalocyanine is completely dissolved and evenly dispersed; weigh 500 g of pretreated activated carbon particles, soak them in the ferrophthalocyanine solution, soak equal volumes for 24 hours, and then dry for use.
[0048] Weigh 15g urea and 500mL deionized water as solvent, stir thoroughly until the urea is completely dissolved; soak 500g of dry activated carbon particles loaded with Fe Pc in the urea solution for 12h and then dry; calcine the dried activated carbon particles in a muffle furnace at high temperature for 4h at a temperature of 520℃ and a heating rate of 5℃ / min. All drying temperatures are 80℃ and the drying time is 6h.
[0049] Example 2
[0050] 600g of granular activated carbon was placed in a 1000mL glass beaker, 1000mL of deionized water was added, and ultrasonic washing was performed, followed by draining, and the loss was minimized. The ultrasonic washing operation was repeated three times, and the solution was clarified during the last washing. After washing, the activated carbon particles were dried in a blast drying oven to obtain the activated carbon particles. The equal volume impregnation method was adopted, and a sufficient amount of 20% nitric acid solution was added, and the activated carbon was impregnated for 10 hours, and then dried in a blast drying oven to obtain the acid-activated AC carrier. The ultrasonic washing operation was repeated three times to wash away the residual acid on the surface of the activated carbon carrier, and the catalyst after ultrasonic washing was placed in a blast drying oven to dry. The ultrasonic power of the deionized water ultrasonic washing was 100W, and the time was 3 hours.
[0051] Weigh 2.4 g of ferrophthalocyanine and 600 mL of anhydrous ethanol as solvent, stir thoroughly until the ferrophthalocyanine is completely dissolved and evenly dispersed; weigh 600 g of pretreated activated carbon particles, soak them in the ferrophthalocyanine solution, soak an equal volume for 24 hours, and then dry them for use.
[0052] Weigh 24g urea and 600mL deionized water as solvent, stir thoroughly until the urea is completely dissolved; soak 600g of dry activated carbon particles loaded with Fe Pc in the urea solution for 12h and then dry; calcine the dried activated carbon particles in a muffle furnace at high temperature for 4h at 520℃ and a heating rate of 5℃ / min. All drying temperatures are 80℃ and the drying time is 6h.
[0053] Example 3
[0054] Place 600g of granular activated carbon in a 1000mL glass beaker, add 1000mL of deionized water, wash ultrasonically, and drain, try to avoid loss, repeat the ultrasonic washing operation three times, and the solution is clear in the last washing; after washing, use a blast drying oven to dry, and then get activated carbon particles; adopt the equal volume impregnation method, add a sufficient amount of 20% nitric acid solution, activate and impregnate for 10h, and then dry in a blast drying oven to get the acid-activated AC carrier, repeat the ultrasonic washing operation three times to wash away the residual acid on the surface of the activated carbon carrier, and put the catalyst after ultrasonic washing into a blast drying oven for drying. The ultrasonic power of deionized water ultrasonic washing is 100W, and the time is 3h. Weigh 3.0g of ferrophthalocyanine, 600mL of anhydrous ethanol as solvent, stir thoroughly until the ferrophthalocyanine is completely dissolved and evenly dispersed; weigh 600g of pretreated activated carbon particles, soak in the ferrophthalocyanine solution, soak in equal volume for 24h, and then dry for use.
[0055] Weigh 30g urea and 600mL deionized water as solvent, stir thoroughly until the urea is completely dissolved; soak 600g of dry activated carbon particles loaded with Fe Pc in the urea solution for 12h and then dry; calcine the dried activated carbon particles in a muffle furnace at high temperature for 4h at 520℃ and a heating rate of 5℃ / min. All drying temperatures are 80℃ and the drying time is 6h.
[0056] The FePc / gC prepared in Example 1 was used 3 N 4 / AC modified cathode for SEM and XPS characterization test and Examples 4-8. The above-mentioned PEC / EC-MFC reaction system was constructed to treat coking wastewater. The wastewater flowed from the bottom water inlet into the anode area filled with activated carbon loaded with Sheva-type electrogenic bacteria. After being treated by anode microorganisms, it flowed into the sand isolation layer and the cathode area for treatment in sequence. Examples 4-7 all applied the above system.
[0057] Example 4
[0058] An electrocatalytic microbial fuel cell (EC-MFC) system was constructed, and the residence time of coking wastewater in the reaction system was controlled to be 10 hours. Sampling and testing were carried out. Figure 1 , a is the TOC data diagram; b is the TN data diagram; c is the NH 4 + a is COD data graph; d is COD data graph.
[0059] Example 5
[0060] The same system as in Example 4 was constructed, but 50 mg / L Na 2 S was used as a supplementary carbon source, and the wastewater retention time in the reaction system was controlled to be 10 hours. Sampling was performed and combined with Figure 2 , a is the TOC data diagram; b is the TN data diagram; c is the NH 4 + a is the data graph; d is the COD data graph.
[0061] Example 6
[0062] The same system as in Example 4 was constructed, but on this basis, 0.03 mM NaCl was added to the raw water, the residence time of the wastewater in the reaction system was controlled to be 10 hours, and sampling was performed. Figure 3 , a is the TOC data diagram; b is the TN data diagram; c is the NH 4 + a is the data graph; d is the COD data graph.
[0063] Example 7
[0064] A photocatalytic / electrocatalytic microbial fuel cell (PEC / EC-MFC) system was constructed, but on this basis, 50 mg / L Na 2 S as a supplementary carbon source, and then the system was tested in succession with aeration, light, PMS and other conditions, and daily sampling and monitoring were performed to check the changes in the effluent; Figure 4 , a is the degradation stability diagram of TOC in coking wastewater; b is the degradation stability diagram of TN in coking wastewater.
[0065] Through this embodiment, it can be seen that after 4 consecutive days of treatment, the TOC of the primary effluent has reached the national primary direct discharge standard, and the TN of the effluent after the secondary treatment has reached the national primary direct discharge standard.
[0066] Example 8
[0067] Combination Figure 5The electrocatalytic ORR system was constructed to conduct four groups of ORR reaction comparison tests. The anolyte in the four groups of experiments was 0.5 M Na 2 SO 4 Solution.
[0068] The first group of cathode electrolytes was 0.5 M Na 2 SO 4 Solution, cathode material is FePc / gC 3 N 4 / AC;
[0069] The second group of cathode electrolyte is 0.5M Na 2 SO 4 Coking wastewater diluted 20 times, cathode material is FePc / gC 3 N 4 / AC;
[0070] The cathode electrolyte of the third group is 0.5M Na 2 SO 4 solution, the cathode material is pure activated carbon particles;
[0071] The fourth group of cathode electrolyte is 0.5MNa 2 SO 4 The raw water of coking wastewater was diluted 20 times, and the cathode material was pure activated carbon.
[0072] When the cathode electrolyte is 0.5 M Na 2 SO 4 Solution, cathode material is FePc / gC 3 N 4 / AC, the system's H 2 O 2 The highest yield is 62.8mg / h / g cat .
[0073] From this example, we can see that the hydrogen peroxide yield of pure activated carbon is extremely low, indicating that the modified cathode has the ability to electrocatalyze ORR to produce H 2 O 2 When the modified cathode is used as the working electrode, it is 2 SO 4 When the coking wastewater is used as the electrolyte, H 2 O 2 Production is reduced.
[0074] This example verifies the FePc / gC 3 N 4 / The principle of AC modified cathode working to treat coking wastewater can generate H in the electrocatalytic process 2 O2 , thereby generating ·OH to oxidize the organic pollutants in the coking wastewater.
[0075] SEM characterization test
[0076] As shown in Figure 6, SEM characterization tests were carried out on the untreated activated carbon and the prepared modified cathode; it can be observed that the surface of pure activated carbon is rough, showing irregular, lamellar, granular and flaky structures; the surface of the modified cathode material is smooth, with more regular pore structures, providing more attachment points for the catalyst, contributing more reaction active sites, and accelerating the reaction process.
[0077] XPS characterization test
[0078] Fe Pc / gC 3 N 4 X-ray photoelectron spectroscopy was performed on the AC before calcination, after calcination, and after reaction. Four elements, C, N, O, and Fe, were observed in the total spectra of the three materials, which was consistent with the composite catalyst. Figure 7 In the figure, b is the high-resolution spectrum of C1s, where three peaks can be seen at 283.6 eV, 284.8 eV and 289.7 eV. These three peaks are CC bonds (sp2), instrumentally adsorbed amorphous carbon and CC / C=C bonds of phthalocyanine ring, and typical sp2 carbon of g-C3N4 (NC=N); c is the high-resolution spectrum of N1s, where three peaks at 398.8 eV, 400.2 eV and 401.6 eV can be observed, which belong to amino N (N-hx), bridging and pyrrole effect between nitrogen atoms and sp2 hybridization (C=NC); d is the high-resolution spectrum of Fe 2p. Although the Fe content is low, it can be clearly observed that the Fe 2p spectrum is convoluted into four peaks at 708.3 eV, 712.1 eV, 721.8 eV and 724.7 eV, respectively, which belong to Fe 2+ 2p 3 / 2 , Fe 3+ 2p 3 / 2 ,Fe 2+ 2p 1 / 2 and Fe 3+ 2p 1 / 2 , indicating that Fe 2+ and Fe 3+ The coexistence of 2,4-dihydro-1,4-dihydro-2-nitrogen and 2,4-dihydro-1,4-dihydro-2-nitrogen species ... confirmed the formation of aromatic nitrogen-coordinated Fe(III) during the ammonia separation process of urea.
[0079] and Figure 7 compared to, Figure 8 It is FePc / gC without calcination 3 N 4 / AC XPS spectrum. Figure 8 In the spectrum b and c, no gC was observed. 3 N 4 The characteristic peaks of the material indicate that g-C3N4 has not been formed at this time.
[0080] and Figure 7 compared to, Fig. 9 It is the Fe Pc / gC after treating wastewater in the reactor 3 N 4 / AC XPS spectrum. Fig. 9 In the c and d spectra, we can observe different Figure 7 The characteristic peaks of Fe-N coordination in spectra c and d indicate that the reaction caused changes in the Fe-N vibration related to pyridine-N, leading to changes in the peaks.
Claims
1. A method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode, characterized in that: Here are the steps: (1) Acid activation pretreatment of activated carbon particles; (2) Preparation of FePc / AC: Ferrophthalocyanine was dissolved in anhydrous ethanol, loaded on activated carbon particles after activation pretreatment by impregnation, and then dried to obtain dry ferrophthalocyanine / activated carbon particles; (3) Preparation of FePc / g-C3N4 / AC: Urea was dissolved in deionized water and loaded on ferrophthalocyanine / activated carbon particles by impregnation. After drying, it was calcined at high temperature in a muffle furnace to obtain carbon nitride-doped ferrophthalocyanine activated carbon.
2. The method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 1, characterized in that: In step (1), the acid activation pretreatment process includes: ultrasonic washing with deionized water, drying, activation immersion with an acid solution, drying, ultrasonic washing with deionized water, and drying.
3. The method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 2, characterized in that: In step (1), the ultrasonic power of the deionized water ultrasonic washing is 80-100W, and the time is 2-4h; the drying temperature is 60-80°C, and the time is 6-8h; the acid solution is a nitric acid solution, and the mass fraction of the nitric acid solution is 15%-20%; and the activation immersion time is 8-10h.
4. The method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 1, characterized in that: In step (2), the mass fraction of FePc relative to the activated carbon particles is 0.3-0.5wt%.
5. The method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 1, characterized in that: In step (2), an equal volume impregnation method is adopted for 12 to 24 hours; and the drying temperature is 60 to 80° C. for 6 to 8 hours.
6. The method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 1, characterized in that: In step (3), the proportion of urea added is 3 to 5 wt% relative to the ferrocyanide / activated carbon particles; an equal volume impregnation method is used for 12 to 24 hours; and the drying temperature is 60 to 80° C. for 6 to 8 hours.
7. The method for preparing a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 1, characterized in that: In step (3), the operating temperature of the muffle furnace calcination is 520-550° C., the heating rate is set to 2-5° C. / min, and the calcination time is 3-4 h.
8. The use of a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode as claimed in any one of claims 1 to 7, characterized in that: Used for electrocatalytic ORR to produce H2O2.
9. The use of a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 8, characterized in that: It is used to construct the PEC / EC-MFC system of the photo / electrocatalytic microbial fuel cell coupling system. The construction process of the PEC / EC-MFC system is as follows: the system has an upper and lower structure, the upper part is the cathode chamber, the lower part is the anode chamber, and there is an isolation layer between the anode chamber and the cathode chamber, and the isolation layer includes two layers of filter cloth and sand filled between the filter cloths; the operation mode of coking wastewater is bottom-in and top-out; the anode chamber of the PEC / EC-MFC system is filled with activated carbon particles loaded with Shewanella electrogenic bacteria, and an aeration head is used at the bottom to disperse the water; the anode conductive material is a carbon rod, one end of which is connected to a wire and then externally connected to a series resistor, an ammeter and a cathode material in sequence, and the cathode conductive material is a carbon rod; the cathode chamber is filled with carbon nitride-doped activated carbon with ferrophthalocyanine, and a visible light source simulating sunlight is added above the cathode when building the PEC-MFC.
10. The use of a carbon nitride-doped ferrophthalocyanine activated carbon-filled modified cathode according to claim 8, characterized in that: Used to construct an electrocatalytic ORR system. The construction of the electrocatalytic ORR system: the two electrolytic cells of the double-tank electrolytic cell are separated by an ion exchange membrane, the anode electrolyte is a Na2SO4 solution, the cathode electrolyte is a Na2SO4 solution, or the cathode electrolyte is diluted coking wastewater with the addition of Na2SO4; a carbon rod is used as the anode, and the prepared carbon nitride-doped ferrophthalocyanine activated carbon is used as the cathode material, and the cathode is connected to the anode through the carbon rod; the cathode material is placed in an insulating container, and the insulating container is connected to the cathode electrolyte; continuous aeration of the cathode ensures a continuous oxygen supply, and continuous ORR experiments are carried out in the constructed electrocatalytic ORR system.
Citation Information
Patent Citations
Preparation method of activated carbon carried carbon-doped graphite phase carbon nitride
CN106179444A
Preparation method of iron phthalocyanine filter cathode membrane for improving electricity generation
CN110808379A
Fluid seawater battery and preparation method thereof
CN111816890A
Preparation and application of hollow carbon nanosphere loaded iron phthalocyanine molecular cluster electro-catalytic material
CN116364956A
Modularized microbial power generation coupling optical / electro-catalysis energy-saving wastewater treatment system with adjustable water level and no need of aeration cathode
CN116495869A
